Still Wanting to Win: Reward System Stability in Healthy Aging - Opitz, Laura; Wagner, Franziska; Rogenz, Jenny; Maas, Johanna; Schmidt, Alexander; Brodoehl, Stefan; Klingner, Carsten M. (Frontiers in Aging Neuroscience, 2022)
Healthy aging is accompanied by multi-faceted changes. Especially within the brain, healthy aging exerts substantial impetus on core parts of cognitive and motivational networks. Rewards comprise basic needs such as food, sleep, or social contact. Thus, a functionally intact reward system remains indispensable for elderly people to cope with everyday life and to adapt to their changing environment. Research shows that reward system function is better preserved in the elderly than most cognitive functions. To investigate the compensatory mechanisms providing reward system stability in aging, we employed a well-established reward paradigm (Monetary Incentive Delay Task) in groups of young and old participants while undergoing EEG measurement. As a new approach, we applied EEG connectivity analyses to assess cortical reward-related network connectivity. At the behavioral level, our results confirm that the function of the reward system is preserved in old age. The mechanisms identified for maintaining reward system function in old age do not fit into previously described models of cognitive aging. Overall, older adults exhibit lower reward-related connectivity modulation, a higher reliance on posterior and right-lateralized brain areas than younger adults, and connectivity modulation in the opposite direction than younger adults, with usually greater connectivity during non-reward compared to reward conditions. We suggest that the reward system has unique compensatory mechanisms distinct from other cognitive functions, probably due to its etymologically very early origin. In summary, this study provides important new insights on cortical reward network connectivity in healthy aging.